Inflation and the Canadian experience : proceedings of a conference - Swan, Neil; Wilton, David A.; Queen's University (Kingston, Ont.). (Kingston, Ont. : Industrial Relations Centre, Queen's University, 1971)
This book arose from a conference on inflation conducted by the Institute for Economic Research at Queen's University in June of 1970.
"Sponsored by the Institute for Economic Research, Queen's University."
Includes bibliographical references.
osc 10/05/2018
Loans
Keywords: Inflation (Finance)